Применение педагогических технологий в процессе формирования социокультурной компетентности студентов из КНР, обучающихся в высших учебных заведениях Республики Беларусь - Берёзко, Д. В. (БНТУ, 2021)
The article discusses pedagogical technologies as a way of forming socio-cultural competence. Based on the results of the theoretical analysis and the ascertaining experiment, the author proves the effectiveness of using the "design technology" method in the formation of socio-cultural competence among Chinese students of law specialties.